Autobiographies of the semi-literate: writing and reading in the memoirs of two peasants between the 19th and 20th centuries - Braida, Lodovica (Bibliothecae.it, 2025)
The essay compares two autobiographies produced in rural contexts between the 19th and 20th C., in order to investigate how writing functions as a means of individual emancipation and identity construction. At the heart of the analysis are the memoirs of Raffaele Codino (1836–1912), from Liguria, and Vincenzo Rabito (1899–1981), from Sicily. While Rabito’s posthumously published autobiography (Terra matta, 2007) has already attracted substantial scholarly attention, nothing was previously known about two works by Raffaele Codino, recently discovered by Marco Francalanci. Francalanci edited these texts, accompanied by a rich introductory essay, in a new edition published by Ronzani (2024). The two works include a fictional narrative, Il trasporto del pensiero, and an autobiographical account entitled Autobiografia della storia della disastrosa vita di Codino Raffaele, both self-published in Savona in 1905 and 1906, respectively. Codino’s autobiography recounts a life marked by paternal abandonment, poverty, and various social and cultural barriers that hindered his access to formal education. Nonetheless, the text also conveys a persistent determination to achieve self-emancipation through writing – rendered in an uncertain Italian, heavily influenced by orality, and characteristic of so-called “semi-literate” authors. Il trasporto del pensiero, by contrast, is a fictional work shaped by Codino’s exposure to popular science and early science fiction literature, which he reinterprets according to his own worldview and sensibilities. A comparison with Rabito’s memoir – written in an oral register imbued with “Sicilianisms” – highlights fundamental differences: while Codino strives to imitate bookish writing, Rabito, a “narrator of pure instinct,” draws expressive power from oral storytelling. His narrative acquires a collective dimension, particularly in the passages recounting his involvement in World War I alongside the “ragazzi del ’99.” For Rabito, writing becomes a tool for personal and generational redemption – a way of making sense of a life “mistreated and much troubled.”